498. MINIMALLY INVASIVE ESOPHAGECTOMY FOR PATIENTS WITH ESOPHAGEAL CANCER AND A HISTORY OF LIVER TRANSPLANTATION: A LITERATURE REVIEW AND CASE SERIES. (24th September 2022) - Uzun, Eren; Grimminger, Peter
Abstract: The survival after liver transplantation is continually improving. With evidence of an increased risk of de-novo malignancies after liver transplantation, it is urgent to improve the treatment of an esophageal cancer in patients with a history of liver transplantation. With this study we wanted to show a case series of totally minimally invasive Esophagectomy for patients with a history of liver transplantation, as well as an literature review. We performed a systematic literature review according to the PRISMA guidance to identify the documented cases of an operative procedure in patients with a history of liver transplantation. Baseline characteristics, tumor stages as well as operative and postoperative management is compared with the case series of 2 cases operated minimally invasive in our center. Seven studies were identified, with a total of 15 patients who underwent esophagectomy after liver transplantation. In 67% of the cases, including our two patients, alcohol associated liver cirrhosis was the indication for the liver transplantation. All reported cases proceed an open surgical approach for the Esophagectomy, except for 1 case with an open abdominal approach and a thoracoscopic chest procedure. The two cases in our center underwent a totally minimally invasive esophagectomy. The mean length of stay in the hospital was 21.5 days, compared to 8 and 14 days in our presented cases. The importance of an optimal treatment of esophageal cancer after liver transplantation is evident. With this case series we showed that it is technically feasible to proceed a total minimally invasive Esophagectomy for patients with a history of liver transplantation in a curative intention. For a successful and radical treatment of malignancies after liver transplantation a multidisciplinary procedure is necessary.